Hygienic-sanitary conditions of school food and nutrition units (Research, Society and Development, 2021)
The Food and Nutrition Units must contribute to maintaining, improving or restoring the health of the clientele served. However, poor hygiene conditions in these places can contribute to the occurrence of foodborne illnesses. This study aims to discuss the results of research on the hygienic-sanitary conditions of Food and Nutrition Units in Brazilian schools. This is an integrative review of articles published between 2017 and 2021, and indexed in LILACS, SciELO and Google Scholar databases. The terms: “good manufacturing practices”, “school feeding”, “food production” and “quality control” and their English versions were used. This review was based on eleven studies, which used the Good Practices checklist to assess and classify the health risk of the analyzed units. Most studies observed that the Food and Nutrition Units of schools in different regions of Brazil had partially adequate hygienic-sanitary conditions, according to the classification of the Resolution of the Collegiate Board No. 275/2002 of the National Health Surveillance Agency. Nonconformities in the locations occurred in all blocks assessed by the studies, being more frequent in buildings and facilities. There is a need for greater attention from health control agencies to the Food and Nutrition Units of schools, considering that the food offered in this environment must be of sanitary and nutritional quality, contributing to the health and academic performance of students.